Determinants of research performance of university academics and the moderating and mediating roles of organizational culture and job crafting - Mohd Rasdi, Roziah; Tauhed, Siti Zainab; Zaremohzzabieh, Zeinab; Ahrari, Seyedali (Emerald Publishing Limited, 2022)
Purpose: This paper aims to identify the role of organizational and individual factors in predicting the research performance of academics when job crafting is a mediator variable and organizational culture is a moderating variable. Design/methodology/approach: This study was conducted by collecting responses from academics at five Malaysian research-based universities. The sample size was 273. Standard questionnaires were used to collect the data. The data were analyzed using partial least squares structural equation modeling. Findings: The most significant predictors of research performance were organizational culture, individual effort and professional development, whereby job crafting was most optimally predicted by work engagement and transformational leadership. While organizational culture moderated the relationship between transformational leadership and research performance, the mediating role of job crafting was insignificant between work engagement and research performance. Research limitations/implications: The findings have important implications for human resource development practitioners (HRD) in terms of improving overall academic research performance. Practical interventions are suggested to assist academics in enhancing their performance. This study highlights how academic performance can be managed more effectively. Originality/value: The findings extend the HRD literature in higher education and offer a framework that enhances the understanding of the organizational and individual factors that influence academics' research performance within a specific context of research universities in a non-Western context.